Towards DNA Nanomachines for Cancer Treatment: Achieving Selective and Efficient Cleavage of Folded RNA. Issue 14 (28th February 2019) - Nedorezova, Daria D.; Fakhardo, Anna F.; Nemirich, Daria V.; Bryushkova, Ekaterina A.; Kolpashchikov, Dmitry M.
Abstract: Despite decades of effort, gene therapy (GT) has failed to deliver clinically significant anticancer treatment, owing in part to low selectivity, low efficiency, and poor accessibility of folded RNA targets. Herein, we propose to solve these common problems of GT agents by using a DNA nanotechnology approach. We designed a deoxyribozyme‐based DNA machine that can i) recognize the sequence of a cancer biomarker with high selectivity, ii) tightly bind a structured fragment of a housekeeping gene mRNA, and iii) cleave it with efficiency greater than that of a traditional DZ‐based cleaving agent. An important advantage of the DNA nanomachine over other gene therapy approaches (antisense, siRNA, and CRISPR/cas) is its ability to cleave a housekeeping gene mRNA after being activated by a cancer marker RNA, which can potentially increase the efficiency of anticancer gene therapy. The DNA machine could become a prototype platform for a new type of anticancer GT agent. Abstract : A mean machine : A deoxyribozyme‐based DNA nanomachine (DNA machine) was developed to bind a fragment of a housekeeping gene mRNA using arms 1–4 and cleave it only in the presence of the cancer marker N‐Myc (see picture). The DNA machine was equipped with RNA‐binding functions for efficient unwinding of folded RNA and can be seen as an initial step towards the development of anticancer gene‐therapy agents based on multifunctional DNA associations.